The health impacts of waste incineration: a systematic review. (18th September 2019) - Tait, Peter W.; Brew, James; Che, Angelina; Costanzo, Adam; Danyluk, Andrew; Davis, Meg; Khalaf, Ahmed; McMahon, Kathryn; Watson, Alastair; Rowcliff, Kirsten; Bowles, Devin
Abstract: Introduction : Waste incineration is increasingly used to reduce waste volume and produce electricity. Several incinerators have recently been proposed in Australia and community groups are concerned about health impacts. An overview of the evidence on health effects has been needed. Method : A systematic review of English language literature for waste incinerators and health using PRISMA methodology. Results : A range of adverse health effects were identified, including significant associations with some neoplasia, congenital anomalies, infant deaths and miscarriage, but not for other diseases. Ingestion was the dominant exposure pathway for the public. Newer incinerator technologies may reduce exposure. Discussion : Despite these findings, diverse chemicals, poor study methodologies and inconsistent reporting of incinerator technology specifications precludes firmer conclusions about safety. Conclusion : Older incinerator technology and infrequent maintenance schedules have been strongly linked with adverse health effects. More recent incinerators have fewer reported ill effects, perhaps because of inadequate time for adverse effects to emerge. A precautionary approach is required. Waste minimisation is essential. Implications for public health : Public health practitioners can offer clearer advice about adverse health effects from incinerators. We suggest improved research design and methods to make future studies more robust and comparable. We offer ideas for better policy and regulation.